Non-targeted metabolomics-mediated elucidation of metabolite changes in Polygonatum kingianum during traditional steaming with black beans - Zhu, Haiyan; Pei, Zaoxia; Zhang, Lei; Dong, Jiahong; Ji, Pengzhang (Frontiers in Nutrition, 2025)
IntroductionPolygonatum is a traditional medicinal and edible plant often prepared by steaming it with ingredients like yellow rice wine and black beans. However, the metabolic changes in Polygonatum kingianum (PK) during the traditional steaming method with black beans have not been previously reported. This study aims to explore how the addition of black beans and the degree of steaming affect the quality of PK.MethodsThis study quantified polysaccharides, reducing sugars, saponins, and flavonoids in PK subjected to varied steaming cycles, while also integrating color measurement, sensory evaluation, and non-targeted metabolomics analysis.ResultsPK is rich in lipids, amino acids, sugars, flavonoids, and organic acids. Notably, we observed the production and significant accumulation of daidzein and daidzin (two primary active compounds derived from black beans) as well as triterpenoid saponins (including Sandosaponin A, Soyasaponin II-III, V, and Pisumsaponin I-II) in steamed PK (p < 0.05). After three steaming cycles, multiple bioactive compounds levels peaked or stabilized, which was consistent with the sensory quality (score: 94/100). Compared to the raw PK, the P3 stage exhibited significant increases in saponins, total sugars, organic acids, and flavonoids by 21.29, 35.02, 49.13, and 44.76%, respectively (p < 0.05), reducing sugars showed a remarkable increase of 160.94-fold (p < 0.01), while polysaccharides decreased significantly by 43.33% (p < 0.01).ConclusionThis study provides the first evidence that steaming with black beans can synergistically increase the diversity of triterpenoid saponins and isoflavones in PK, with the optimal quality achieved after three rounds of steaming. These findings validate the scientific efficacy of the traditional processing method. Our results advocate for the continued use of the black bean steaming method to enhance the nutritional and health-promoting value of PK, while also providing a template for the innovation of herbal processing techniques based on auxiliary ingredients.